Can Individuals With Alcohol Use Disorder Sustain Non-abstinent Recovery? Non-abstinent Outcomes 10 Years After Alcohol Use Disorder Treatment. Issue 4 (July 2021) - Witkiewitz, Katie; Wilson, Adam D.; Roos, Corey R.; Swan, Julia E.; Votaw, Victoria R.; Stein, Elena R.; Pearson, Matthew R.; Edwards, Karlyn A.; Tonigan, Jeffrey Scott; Hallgren, Kevin A.; Montes, Kevin S.; Maisto, Stephen A.; et al.
Abstract : Objective: Four decades ago, the "controlled drinking" controversy roiled the alcohol field. Data have subsequently accumulated indicating that nonabstinent alcohol use disorder (AUD) recovery is achievable, but questions remain whether it is sustainable long-term. This study examined whether nonabstinent recovery at 3 years after AUD treatment is associated with better functioning at 10 years after treatment. Methods: Data were from the 10-year follow-up of Project MATCH (New Mexico site only, n   =  146; 30.1% female, 58.6% non-White). Recovery was defined by latent profile analyses based on psychosocial functioning and alcohol consumption 3 years after treatment. Drinking practices and consequences, depression, purpose in life, and anger were assessed 10 years after treatment. Distal outcome analyses examined differences in drinking and functional outcomes at 10 years as a function of the 3-year latent profiles. Analyses were preregistered at https://osf.io/3hbxr . Results: Four latent profiles identified at 3 years after treatment (ie, low functioning frequent heavy drinkers, low functioning infrequent heavy drinkers, high functioning heavy drinkers, and high functioning infrequent nonheavy drinkers) were significantly associated with outcomes 10 years after treatment. The 2 high functioning profiles at 3 years had the highest level of psychological functioning at 10 years posttreatment, regardless of alcohol consumption level. Abstinence at 3 years did not predict better psychological functioning at 10 years. Conclusions: Nonabstinent AUD recovery is possible and is sustainable for up to 10 years after treatment. The current findings align with recent proposals to move beyond relying on alcohol consumption as a central defining feature of AUD recovery. Abstract : Supplemental Digital Content is available in the text